2021
DOI: 10.1111/tpj.15231
|View full text |Cite
|
Sign up to set email alerts
|

Plastidial acyl carrier protein Δ9‐desaturase modulates eicosapentaenoic acid biosynthesis and triacylglycerol accumulation in Phaeodactylum tricornutum

Abstract: SUMMARY The unicellular marine diatom Phaeodactylum tricornutum accumulates up to 35% eicosapentaenoic acid (EPA, 20:5n3) and has been used as a model organism to study long chain polyunsaturated fatty acids (LC‐PUFA) biosynthesis due to an excellent annotated genome sequence and established transformation system. In P. tricornutum, the majority of EPA accumulates in polar lipids, particularly in galactolipids such as mono‐ and di‐galactosyldiacylglycerol. LC‐PUFA biosynthesis is considered to start from oleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Thus, homology modeling and docking are the essential methods to analyze the structure of bacterial membrane fatty acid desaturases and elongase in the current state (21). Herein, we summarized the research approach of homology modeling and docking based on the previous work (21)(22)(23)55). First, after homology analyzes the amino acid sequence, the scientist can determine templates with higher homology and resolution in the protein database (e.g., Protein Data Bank, PDB).…”
Section: Structure Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, homology modeling and docking are the essential methods to analyze the structure of bacterial membrane fatty acid desaturases and elongase in the current state (21). Herein, we summarized the research approach of homology modeling and docking based on the previous work (21)(22)(23)55). First, after homology analyzes the amino acid sequence, the scientist can determine templates with higher homology and resolution in the protein database (e.g., Protein Data Bank, PDB).…”
Section: Structure Analysis Methodsmentioning
confidence: 99%
“…Another study of homology modeling and docking also showed that four α-helices constitute the catalytic site and transmembrane domain in Δ9-desaturase from Arthrospira platensis ( 55 ). Beyond that, 3D structure modeling studies revealed that three variant amino acids (F160, A223, and L156) in domain Δ9-desaturase encoded by gene PtAAD narrow the space of substrate binding center, explaining the reason of substrate preference of this especial Δ9-desaturase for palmitic acid ( 22 , 23 ) ( Table 2 ).…”
Section: Vital Desaturase In ω-6 and ω-3 Pathwaymentioning
confidence: 99%
“…Using pulse-chased experiments with [ 14 C] fatty acids, Arao and Yamada [7] proposed the predominant route of EPA biosynthesis in P. tricornutum. The first step in this pathway is ∆6-desaturation of linoleic acid (LA; 18:2 ∆9,12 ) to γ-linolenic acid (GLA; 18:3 ∆6,9,12 ), which is then ∆15-desaturated to produce stearidonic acid (SDA; 18:4 ∆6, 9,12,15 ). SDA is elongated by two carbons and desaturated to yield eicosapentaenoic acid (EPA; 20:5 ∆5, 8,11,14,17 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, P. tricornutum produces DHA in trace levels only [6]. After biosynthesis in the endoplasmic reticulum, EPA can be transported to the plastid and incorporated into galactolipids, especially MGDG and DGDG [8,9]. The mechanism of trafficking EPA between the endoplasmic reticulum and plastid is unclear and requires further investigations [1,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation